"JURUS SAKTI" Dental Caries Prevention Education Program: A One-Group Pre-Test Post-Test Study on Knowledge Improvement Among Vocational School Adolescents in Batang, Indonesia - Erdianto Wardhana; Erwid Fatchur Rahman; Muhammad Dian Firdausy (Unram Journal of Community Service, 2026)
Widespread daily toothbrushing, Indonesian adolescents continue to demonstrate poor preventive practice, reflecting a critical knowledge-practice gap. This study evaluated the effectiveness of the "JURUS SAKTI" structured caries prevention education program on knowledge among students of SMK Al-Sya'iriyah, Limpung, Batang. A one-group pre-test post-test quasi-experimental design was employed with 32 participants (10 males, 22 females). The JURUS SAKTI program comprised four interactive modules covering correct toothbrushing technique, sugar consumption awareness, fluoride use, and the importance of routine dental visits. Knowledge was assessed using a structured questionnaire administered before and immediately after the intervention. Data were analyzed using the Wilcoxon Signed Ranks Test. Results showed a statistically significant improvement in mean knowledge scores from 51.56 (±10.66) pre-intervention to 79.69 (±10.70) post-intervention (Z = −4.946, p < .001), with a large effect size (r = 0.874). Knowledge categorization revealed a complete transformation: participants classified as "Good" increased from 0% to 65.6%, while none remained in the "Poor" category post-intervention. The JURUS SAKTI program is an effective, practical, and replicable model for caries prevention education in community settings.